Organizations are people: reflections, obstacles and learning opportunities. Issue 6 (4th September 2020) - Robinson, Graham
Abstract : Purpose: The purpose of this paper is to place the idea of the learning organization in a historical, multidisciplinary context with the aim of identifying obstacles and opportunities for its greater realization in practice. Design/methodology/approach: Marking the 30th anniversary of publication of Peter Senge's "The Fifth Discipline", the paper reflects on approaches to the study and analysis of organizations over the past century from German sociology, human relations, organization development, the learning organization to responses to the Covid-19 pandemic. Findings: It is suggested that distributed leadership is critical to the realization of organizational learning and its absence is a major inhibitor of such learning. Following Argyris, it is argued that high levels of skill (personal mastery) may, in some circumstances, provide a barrier to organizational learning in the face of contextual uncertainty and change. Research limitations/implications: While no specific areas of research are proposed, questions are raised which may only be answered in the wake of appropriate (interdisciplinary) research. Practical implications: The reflective nature of the paper suggests that significant reform is required in the legislation that encourages short-term thinking on the part of institutional investors to the detriment of strategic thinking and long-term planning. Social implications: The Covid-19 pandemic seems to have provided an opportunity to redress a perceived imbalance between traditional organizational thinking and opportunities demonstrated by effective community action, for reappraisal of organizations as communities of people as well as being formalized structures, systems and processes. Originality/value: This paper seeks to synthesize diverse theories of organization with the aim of stimulating further innovation in approaches to organizational learning.